Isolasi dan Uji Aktivitas Antiinflamasi Ekstrak Daun Andong (Cordyline fructicosa (L) A.Chev) - Endah Nurrohwinta Djuwarno; Hamsidar Hasan; Faramita Hiola; Dewa Ayu Puspita; Mahdalena Sy. Pakaya (Journal Syifa Sciences and Clinical Research, 2022)
Andong (Cordyline fructicosa (L) A. Chev) is used as traditional medicine, the use of this traditional medicine is related to the content of secondary metabolites contained in the andong plant. Empirically people use this plant as an antioxidant, the compound that acts as an antoixidant is related to antiinflamasi. The purpose of this study was to isolate secondary metabolites from the extracts of N-Hexane, Ethyl Acetate, and Methanol from Andong (Cordyline fructicosa (L) A. Chev) leaves and to determine the anti-inflamatory effect of the isolated secondary metabolites of Andong (Cordyline fructicosa (L) A. Chev) leaves through in vitro with red blood cell stabilization method. Several methods are used in the isolation of these compounds, namely extraction, identification of compound, fractionation of KCV and KKG, KLT,KLTP, and characterizationof compounds using UV-VIS spectrophotometry and FTIR. The results of UV-VIS characterization show a maximum wavelength of 434 nm, and the results of  FTIR characterization indicate the presence of a functional groups namely O-H (Hidroxyl) at a wave number of 3448,72 cm-1, C-H (Aliphatic) at a wave number of 2954,95 cm-1, 2920,23 cm-1, and 2852,72 cm-1, aliphatic compounds are supported by the presence of CH2 and CH3 at wave number of 1463,97 cm-1 and 1379,10 cm-1, C=O (conjugated carbonyl) at wave number of 1721,79 cm-1, C=C at wave number of 1633,71 cm-1, C-O at wave number of 1294,24 cm-1. So it is very likely that the compounds in Andong leaves isolate are flavonoid compounds. Furthermore, the activity of results of the isolation is tested where the isolate whit a concentration of 100 ppm signifies the highest anti-inflamatory activity, with the ability to stabilize red blood cell membranes of 80,142 %.